Identities and teaching positions in the teacher-university relationship: A focus group study with teachers at the National Autonomous University of Mexico - Benavides-Lara, Mario; de Aguero-Servín, Mercedes; Rendón-Cazales, Víctor; Pompa-Mansilla, Maura (Education Policy Analysis Archives, 2022)
The aim of this work is to identify the way in which the university affects the identity formation of its teachers by analyzing the positions they assume in relation to the institution as a mediator in the construction of their experiences and trajectories. To carry out the analysis, conceptually, we resorted to works on intersectionality, institutional analysis and the concept of positions that comes from discourse analysis. The methodological design was based on eight focus groups in which 86 high school and undergraduate teachers from the National Autonomous University of Mexico participated. The results show that, in addition to the teaching positions of inclusion and belonging, there are teaching positions of differentiation, exclusion and inequality that contribute to understanding the ways in which teachers relate to the university. Finally, a call is made to make visible the institutional structures that generate these forms of exclusion and inequality.